Electron heating induced by an ac-bias current in the regime of Shubnikov–de Haas oscillation in the high mobility GaAs/AlxGa1−xAs two-dimensional electron system. (10th July 2018) - Munasinghe, C Rasadi; Gunawardana, B; Samaraweera, R L; Wang, Z; Nanayakkara, T R; Kriisa, A; Reichl, C; Wegscheider, W; Mani, R G
Abstract: The magnetotransport properties of the high mobility GaAs/AlGaAs two-dimensional electron gas systems have been examined to determine the influence of the ac current bias on the carrier temperature. The changes in the line shape of Shubnikov–de Haas oscillations in the longitudinal magnetoresistance ( ) were followed as a function of the ac current bias in the temperature range of in order to determine the carrier heating effect due to the ac bias. The lineshape analysis of these oscillations indicates that the carrier temperature of the two-dimensional electron system is linearly proportional to the ac bias current.